2015
DOI: 10.5811/westjem.2015.8.27467
|View full text |Cite
|
Sign up to set email alerts
|

The Physiologically Difficult Airway

Abstract: Airway management in critically ill patients involves the identification and management of the potentially difficult airway in order to avoid untoward complications. This focus on difficult airway management has traditionally referred to identifying anatomic characteristics of the patient that make either visualizing the glottic opening or placement of the tracheal tube through the vocal cords difficult. This paper will describe the physiologically difficult airway, in which physiologic derangements of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
172
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(182 citation statements)
references
References 90 publications
0
172
0
10
Order By: Relevance
“…However, patients experiencing arterial desaturation had higher mortality as compared to controls. Not surprising, hypoxemia results in added stress to an already stressed system, which could result in unwanted consequences as illustrated in the literature (35)(36)(37). In addition, it's been shown that proning patients decreases mortality and the major physiologic impact is an increase in their arterial oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients experiencing arterial desaturation had higher mortality as compared to controls. Not surprising, hypoxemia results in added stress to an already stressed system, which could result in unwanted consequences as illustrated in the literature (35)(36)(37). In addition, it's been shown that proning patients decreases mortality and the major physiologic impact is an increase in their arterial oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Critical patient may present, mainly, hypoxemia, severe metabolic acidosis, hypotension, and right ventricular insufficiency [9,16,19,20], with a degree of hemodynamic instability resulting in a low cardiopulmonary reserve, in addition to a full stomach, etc., and the implementation of a package of measures for intubation can reduce the incidence of life-threatening complications from 32 to 17% (p = 0.01) during intubation (biblioUCI46). This package of measures should consist of 10 key points ( Table 2).…”
Section: Post-intubationmentioning
confidence: 99%
“…Although there is insufficient evidence, adrenaline diluted at a concentration of 1-10 mcg mL −1 , to be administered in boluses of 10-50 mcg, may be most indicated because of its inotropic effect [16,109,110,113,114].…”
Section: Hypotensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mosier y cols 12 , han conceptualizado este fenóme-no bajo el término "vía aérea fisiológicamente difícil". Esto se refiere a que la presencia de estas alteraciones fisiológicas representadas por: hipoxemia, hipotensión, acidosis metabólica severa y falla ventricular derecha, pueden constituir un tipo de dificultad que también puede conducir a complicaciones y que es necesario pesquisar y compensar antes de manejar la vía aérea 13 .…”
unclassified